The role of lactylation in breast cancer development: mechanisms, clinical translation and new strategies for treatment - Lu, Yanzhen; Yang, Xiaoting; Tan, Lulu; Yang, Yunfei; Yu, Dan; Feng, Gang; Tan, Yuyan (Frontiers in Oncology, 2025)
Worldwide, breast cancer (BC) is a common and deadly illness that poses a serious risk to women’s health. Its development is intimately associated with tumor microenvironment (TME) alteration and metabolic problems. Lactic acid, a principal byproduct of glycolysis, not only facilitates the acidity of the TME but also interferes with cellular circadian rhythms. Moreover, it exerts multifaceted regulatory effects on breast cancer growth by facilitating a new post-translational modification(PTM)ficatio lactylation (Kla). By accelerating metabolic reprogramming, encouraging immunological microenvironment dysregulation, and intensifying tumor growth, metastasis, and chemoresistance, Kla has been shown in studies to contribute to the advancement of BC and poor prognosis. Lactate production and transport, especially targeting lactate dehydrogenase (LDH) and monocarboxylate transporter protein (MCT), show promise in BC treatment. Both tumor-suppressive and immunotherapy-enhancing effects are exhibited by inhibitors that target LDH and MCTs, and they may work in concert with immunotherapy. The function of Kla in BC, its underlying processes, and the possibility of treating the condition by specifically targeting Kla are all examined in this review. Additionally, it suggests the creation of precision-targeted treatments, providing fresh viewpoints on metabolic treatments and combination treatments for BC.